2017
DOI: 10.1016/j.celrep.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxybutyrate Deactivates Neutrophil NLRP3 Inflammasome to Relieve Gout Flares

Abstract: Summary Aging and lipotoxicity are two major risk factors for gout that are linked by the activation of NLRP3 inflammasome. Neutrophil-mediated production of IL-1β drives gouty flares that cause joint destruction, intense pain, and fever. However, metabolites that impact neutrophil inflammasome remain unknown. Here we identified that ketogenic diet (KD) increases beta-hydroxybutyrate (BHB) and alleviates urate crystal induced gout without impairing immune-defense against bacterial infection. BHB inhibited Nlrp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
231
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(241 citation statements)
references
References 47 publications
4
231
4
2
Order By: Relevance
“…D-F, Lentiviral interference vector of GPR109A inhibited the BHBA-mediated change in APP and NEP mRNA expression (n = 3, means ± SD, Student's t test, **P < .01, ***P < .001). The primary circulating ketone is 3-hydroxybutyrate or BHBA, which has been demonstrated to show an anti-inflammatory effect in various diseases 28,29 contributing to its neuroprotective effects. H,I, Quantitative analysis of the expression of APP and NEP in HT22 cells in different groups (n = 3, means ± SD, Student's t test, *P < .05, **P < .01, ***P < .001) other than the treatment of epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…D-F, Lentiviral interference vector of GPR109A inhibited the BHBA-mediated change in APP and NEP mRNA expression (n = 3, means ± SD, Student's t test, **P < .01, ***P < .001). The primary circulating ketone is 3-hydroxybutyrate or BHBA, which has been demonstrated to show an anti-inflammatory effect in various diseases 28,29 contributing to its neuroprotective effects. H,I, Quantitative analysis of the expression of APP and NEP in HT22 cells in different groups (n = 3, means ± SD, Student's t test, *P < .05, **P < .01, ***P < .001) other than the treatment of epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using longitudinal cohort data found higher levels of IL1Beta and IL‐6 were correlated to age‐related illnesses and shorter lifespan (Furman et al ., 2017). Another study showed inhibition of serum IL‐1β alleviated gout‐related symptoms (aging‐related inflammatory disease) in monosodium urate (MSU) crystals‐induced murine model (Goldberg et al ., 2017). Therefore, inhibition of SASP will be critical for limiting inflammaging.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, BHB has been shown to suppress K + efflux, thus dampening NLRP3 inflammasome activation in macrophages . A later study also has revealed BHB blocks the priming and assembly steps of the NLRP3 inflammasome in neutrophils …”
Section: Metabolic Reprogramming Controls Inflammasome Activationmentioning
confidence: 95%